The status of religious instruction in public elementary schools in Angeles City - Manaloto, Abner C. (Animo Repository, 1997)
This study is an assessment of the current situation of the religious instruction program in the public elementary schools in Angeles City, based on Stufflebeam's Context, Input, and Process model of evaluation and designed a modified pastoral plan specific to the teaching of religion in public elementary schools in Angeles City.The study made use of the descriptive-evaluative method of research. It evaluates the existing religious instruction program in public elementary schools in Angeles City. Data were gathered through questionnaires, interviews and documentary investigations. Data analysis included frequency tally, percentage, mean and ranking.The respondents of the study covered 1,060 students and religion teachers. Of the 1,060 are 978 grade VI pupils and 82 are catechists/religion teachers.The study revealed that out of 37 elementary public schools in Angeles City only 13 implement religious instruction program and out of 37 schools, 24 were not reached by the parishes concerned for religious instruction. Reasons given for the failure to implement religious instruction program in the schools are: lack of volunteer catechists, lack of funds, lack of support from school administrators, far distance of other schools, and some school heads do not welcome the religious instruction program. Pupil and catechist respondents strongly agree that religious instruction is very important and that they believe so much on the spiritual value of the religious instruction program. The study concluded that: a) The failure to reach other public elementary schools in Angeles City reveals that parishes still overlooked the importance of a religious instruction program into the development of the child especially in the aspect of values development. b) The specific objectives of the religious instruction program show the linkage of the program with the goals of the Church and therefore, such may really lead into the formation of an appropriate Christian life necessary for the pupils' growth. c) The female dominated volunteer catechists may show that women are more inclined to this catechetical work. Generally, men in the Filipino society still remain to be more of the bread-winner genre and this volunteer service may not be within their capacity. d) The findings show that application of the human evocative approach in the religious instruction, proves that the type of instruction imparted is experimental in orientation. The use of the Bible by almost everyone in teaching religion clearly indicates how religious instruction could propagate a life with and for Christ.